Global Finite-Time Stabilization for Nonholonomic Mobile Robots Based on Visual Servoing. (12th November 2014) - Chen, Hua; Ding, Shihong; Chen, Xi; Wang, Lihua; Zhu, Changping; Chen, Wen
In this paper, the global finite-time stabilization problem is considered for nonholonomic mobile robots based on visual servoing with uncalibrated visual parameters, control direction and unmatched external disturbances. Firstly, the simple dynamic chained-form systems is obtained by using a state and input transformation of the kinematic robot systems. Secondly, a new discontinuous switching controller is presented in the presence of uncertainties and disturbances, it is rigorously proved that the corresponding closed-loop system can be stabilized to the origin equilibrium point in a finite time. Finally, the simulation results show the effectiveness of the proposed control design approach.